2019
DOI: 10.1016/j.compositesb.2019.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects on the durability and the mechanical performance of flax fiber/bio-epoxy composites

Abstract: The growing usage of bio-composite materials in different engineering applications demands a thorough understanding of their performance during their service. Extreme environmental conditions, such as warm, humid, and freezing environments, among others, can degrade the mechanical properties of the bio-composites when they are exposed to harsh environmental conditions. In addition, the use of these composites in underwater applications can also shorten their life cycle. In this work, the durability and mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(83 citation statements)
references
References 30 publications
(36 reference statements)
7
76
0
Order By: Relevance
“…Natural fiber-reinforced composites (NFRPs) have received growing attention in the last decades, both from the academic world and from industries, thanks to their specific mechanical properties, reduced cost and advantages for health and recyclability. Nevertheless, this class of innovative materials shows also some drawbacks, such as their limited aging resistance in humid or wet environmental conditions, i.e., an extensive literature shows that NFRP materials experienced dramatic degradation of their quasi-static mechanical properties when exposed to these environments [10][11][12][13][14][15][16][17][18]. This can be partially ascribed to the softening and plasticization phenomena of natural fibers and thermoset matrix [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Natural fiber-reinforced composites (NFRPs) have received growing attention in the last decades, both from the academic world and from industries, thanks to their specific mechanical properties, reduced cost and advantages for health and recyclability. Nevertheless, this class of innovative materials shows also some drawbacks, such as their limited aging resistance in humid or wet environmental conditions, i.e., an extensive literature shows that NFRP materials experienced dramatic degradation of their quasi-static mechanical properties when exposed to these environments [10][11][12][13][14][15][16][17][18]. This can be partially ascribed to the softening and plasticization phenomena of natural fibers and thermoset matrix [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we investigate the influence of hydrothermal ageing on the fatigue behaviour of a purely unidirectional flax epoxy composite. Indeed, the influence of hydrothermal ageing has been poorly studied whether on the static properties [15][16][17][18][19] or cyclic behaviour [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Assarar et al [23] observed on a flax/epoxy laminate after 40 days of immersion at room temperature a decrease in tensile strength and modulus of 25% and 39% respectively and an increase in strain at failure of approximately 63%. Moudood et al [18] reported a decrease by 9% and 57% for the tensile strength and modulus, respectively, for a unidirectional flax/bio-epoxy composite after immersion until saturation. Li and Xue [15] studied the influence of water immersion time and temperature on the tensile properties of an unidirectional flax/epoxy composite.…”
Section: Introductionmentioning
confidence: 99%
“…Bio-sourced materials, the most abundant resources on the planet, are emerging as reinforcing materials for composites, which have attracted much scientific and industrial attention owing to their attractive advantages such as renewability, biodegradability, sustainability, low density, low cost and better mechanical properties [1][2][3][4][5]. At present, the most common reinforcing material is glass fibers, but the manufacturing process of glass fibers and their products is harmful to the human body, such as dermal and respiratory irritation, and even cancer [6][7][8].…”
Section: Introductionmentioning
confidence: 99%